Bringing (Contingent) Loss Aversion Down to Earth — A Comment on Gal & Rucker's Rejection of "Losses Loom Larger Than Gains". Issue 3 (20th April 2018) - Simonson, Itamar; Kivetz, Ran
Abstract : Although we disagree with some of Gal and Rucker's (2018 – this issue) specific evidence and with their overstated conclusion regarding loss aversion, their overarching message makes a worthwhile contribution. In particular, loss aversion is less robust and universal than has been assumed while its most prominent empirical support — the endowment effect and the status quo bias — is susceptible to multiple alternative explanations. Instead of accepting loss aversion as true unless proven otherwise, we should treat it like other decision properties and psychological accounts that are contingent on various moderators and call for an analysis of psychological mechanisms. In this commentary, we suggest that gatekeepers, such as reviewers, tend to favor loss aversion and other widely accepted tendencies, while demanding a much higher support‐threshold for alternative or newer accounts. Although building on prior theories and concepts is of course important, the bias in favor of incumbent assumptions can impede scientific progress, bar new ideas from the literature, and reinforce well‐established but contingent notions that may apply under some conditions but not others. Abstract : This article is part of a Research Dialogue: Shavitt (2018): https://doi.org/10.1002/jcpy.1054 Gal & Rucker (2018): https://doi.org/10.1002/jcpy.1047 Higgins & Liberman (2018): https://doi.org/10.1002/jcpy.1045 Gal & Rucker (2018): https://doi.org/10.1002/jcpy.1044